Impact of CRM, IMC, and PE on Purchase Intentions: Evidence from the Real Estate Market of Bangladesh - Haque, A K M Kamrul; Amin, Md. Khaled; Parvez, Asif (AIUB Journal of Business and Economics, 2017)
This study sought to identify the relative roles of Customer Relationship Management (CRM), Integrated Marketing Communication (IMC), Customer Referral Campaign (CRC) and Perceived Experience (PE) in the formation of the Purchase Intentions (PI) of Bangladeshi consumers. A total of 111respondents were literally categorized into apartment owners and prospective buyers, were eventually surveyed with the structured and self-administrated questionnaires followed by few in-depth interviews. The results of the study suggest that the three variables; CRM, IMC and PE appear to have significant direct impact on the formation of the Purchase Intentions (PI) of the apartment in Dhaka city. Conversely, CRC found to have no effect on the Purchase Intention (PI).